In-situ (trans)esterification of lipid-dense post-hydrolysis rice bran at ambient pressures with low acid loading. (December 2021) - Go, Alchris Woo; Quijote, Kristelle L.; Gunarto, Chintya; Ju, Yi-Hsu; Angkawijaya, Artik Elisa; Santoso, Shella Permatasari; Agapay, Ramelito C.
Abstract: Dilute acid hydrolysis was employed to generate lipid-dense post-hydrolyzed rice bran (PHRB) which was utilized as feedstock in biodiesel production. Upon drying of the wet PHRB with the entrained dilute acid solution, subsequent carbonization and sulfonation occurred with the material, incorporating significant amounts of sulfur in PHRB as sulfonic acid. The collected dry PHRB was utilized as feedstock in the in-situ (trans)esterification (ISTE) of its lipids to fatty acid methyl esters (FAME), whereby the available acid sites reduced the acid catalyst to be loaded in the reaction system. The optimum reaction conditions under ambient pressures were determined via the Taguchi method and the highest yield achieved was 22.38 ± 0.28 g FAME/100 g PHRB (82.31% conversion or reaction yield), and was achieved at 65 °C, SSR of 20 mL methanol/g dried PHRB, 12 h reaction time, and 5 wt% H2 SO4 of the PHRB processed. The post-ISTE PHRB was found to still possess the catalytic activity and could be used for the esterification of oleic acid and methanol and appreciable stability. Finally, the FAME-rich product also exhibits free-radical scavenging activity, owing to the presence of bioactive components, which may provide better oxidative stability or could be further recovered as high-value by-products. Highlights: Lipid-dense rice bran (RB) for the production of fatty acid methyl esters (FAME). Pre-functionalized post-hydrolysis RB (PHRB) with catalytic activity. In-situ FAME production using PHRB with low catalyst loading. Functionalized PHRB residues as solid acid catalyst for FAME synthesis. FAME-rich crude product with free-radical scavenging activity.